Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jcma.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect against focal cerebral ischemia injury in acute phase of a novel invasive device for regional hypothermia

Abstract: Our findings indicated that the device can effectively achieve regional hypothermia and could be beneficial for patients with cerebral ischemia during the acute phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…These protective mechanisms have been covered in less detail in LH studies compared to those using systemic TH, but encouraging initial evidence suggests that these targets are similarly affected by LH application after stroke. So far, neuroprotective mechanisms validated by both LH and systemic TH stroke studies include modulation of immune function and activity (Kurisu et al, 2016; Liu et al, 2016, 2018), cell death processes (Chang et al, 2015; Liu et al, 2016; Sun et al, 2015; Wu et al, 2017), BBB permeability (Sun et al, 2013, 2015), edema (Gao et al, 2015; Kurisu et al, 2016; Zhao et al, 2013), as well as up‐regulation of cell survival pathways and neurogenesis (Corey et al, 2019).…”
Section: Focal Versus Systemic Th Treatment: a Brief Mechanistic Comparisonmentioning
confidence: 99%
“…These protective mechanisms have been covered in less detail in LH studies compared to those using systemic TH, but encouraging initial evidence suggests that these targets are similarly affected by LH application after stroke. So far, neuroprotective mechanisms validated by both LH and systemic TH stroke studies include modulation of immune function and activity (Kurisu et al, 2016; Liu et al, 2016, 2018), cell death processes (Chang et al, 2015; Liu et al, 2016; Sun et al, 2015; Wu et al, 2017), BBB permeability (Sun et al, 2013, 2015), edema (Gao et al, 2015; Kurisu et al, 2016; Zhao et al, 2013), as well as up‐regulation of cell survival pathways and neurogenesis (Corey et al, 2019).…”
Section: Focal Versus Systemic Th Treatment: a Brief Mechanistic Comparisonmentioning
confidence: 99%
“…lower than that in the control group, which indicated a certain inhibitory effect of mild hypothermia on brain inflammation. At the same time, associated animal experiments indicated that local hypothermia treatment may reduce the area of cerebral infarction(27,28). With the continuous improvement of scientific research, an increasing number of studies…”
mentioning
confidence: 99%